Kebijakan Dividen sebagai Jembatan Finansial: Analisis Jalur antara Profitabilitas, Leverage, dan Nilai Perusahaan - Syaibani, Muhammad Firnanda; Hariyanti , Widi; Siddiq , Faiz Rahman (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
The purpose of this research is to identify the relationship between business value, profitability, and leverage via the mediation of dividend policy. Companies dealing in basic materials that are listed on the Indonesia Stock Exchange from 2020 to 2023 make up the population in this research. Using a purposive sampling technique, 89 samples were collected over a 4-year period from 29 different firms for this research. Multiple linear regression and path analysis in SPSS version 21 were the data analytic techniques used in this study. This study found that leverage has no effect on dividend policy, profitability has no effect on firm value, dividend policy has no effect on firm value, profitability has no effect on dividend policy, firm value is affected by both leverage and profitability, and dividend policy cannot mediate the effect of either on firm value.